Priming treatments for improvement of germination and emergence of cotton seeds at low temperature - Cokkizgin, Hatice; Bölek, Yüksel (Plant Breeding and Seed Science, 2015)
Early sowing in cotton is important for obtaining a high and qualiy yield. Since cotton prefers high temperatures to have a good stand establisment, this work is important to determine better performing genotypes or to promote germination and emergence at low temperatures (<20°C). This research aimed to increase seed germination rate and seed vigour under cold stress conditions. Two cotton genotypes belonging to G. hirsutum L. species (Aydin-110 and Paymaster-2379) were primed with PEG-6000 (200, 300, 400 giL), KN03 (2, 3, 4%), KH2P04 (0.3, 0.4, 0.5 M), NaCl (2, 3, 4%) or Mannitol (2, 4, 6%) to determine the best priming medium and its best amount. After priming, seeds were germinated in germination cabin at cold (18°C) and warm (30° C) temperatures and some characteristics (germination rates, radicle length, hypocotyl length and seedling length) were analyzed. Priming with KN03 (4% or 2%) was found to result in the highest germination rates in both cotton genotypes. The seeds of the genotypes were also primed with 5-aminolevulinic acid (ALA) (1, 10, 25 mg/L), gibberellic acid (GA3) (100, 250, 500 µM), methyljasmonate (MeJA) (1, 3, 5 µM),acetylsalicylic acid (ASA) (1, 10, 100 µM) or kinetin (1, 5, 10 mg/L) added to KN03 (4%) medium to choose the most effective plant growth regulator (PGR) application and its dose. PGRs were observed to have reverse effects on germination rate. Finally, emergence test was conducted with KN03 (4%) and KN03 (2%) using metabolic chill test, and some traits (radicle length, radicle weight, hypocotyllength, hypocotyl weight, seedling length, seedling fresh weight and seedling dry weight) were examined. Our results suggested that priming with KN03 (2%) might be an effecient way to have vigourous cotton plants under the cold stress.